1992
DOI: 10.1128/jb.174.10.3133-3139.1992
|View full text |Cite
|
Sign up to set email alerts
|

Coexpression of UmuD' with UmuC suppresses the UV mutagenesis deficiency of groE mutants

Abstract: The GroE proteins of Escherichia coli are heat shock proteins which have also been shown to be molecular chaperone proteins. Our previous work has shown that the GroE proteins of E. coli are required for UV mutagenesis. This process requires the umuDC genes which are regulated by the SOS regulon. As part of the UV mutagenesis pathway, the product of the umuD gene, UmuD, is posttranslationally cleaved to yield the active form, UmuD'. In order to investigate what role the groE gene products play in UV mutagenesi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
36
0

Year Published

1992
1992
2019
2019

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 58 publications
(38 citation statements)
references
References 29 publications
2
36
0
Order By: Relevance
“…There is strong evidence that GroE interacts with the polymerase subunit of Pol V and protects it from degradation (10). Because Pol IV is a homolog of Pol V, it seemed likely that GroE would also interact with Pol IV, but we failed to detect an interaction between GroE and Pol IV using three methods: coimmunoprecipitation, copurification on a metal resin, and yeast two-hybrid analysis.…”
Section: Discussionmentioning
confidence: 50%
“…There is strong evidence that GroE interacts with the polymerase subunit of Pol V and protects it from degradation (10). Because Pol IV is a homolog of Pol V, it seemed likely that GroE would also interact with Pol IV, but we failed to detect an interaction between GroE and Pol IV using three methods: coimmunoprecipitation, copurification on a metal resin, and yeast two-hybrid analysis.…”
Section: Discussionmentioning
confidence: 50%
“…High levels of epsilon and RNase Hi may also affect DNA repair and mutagenesis by depleting cellular reserves of HSPs. For example, GroEL and GroES stabilize the UmuC protein, which is required for SOS mutagenesis (11). Since GroEL has been shown to act catalytically with DnaK, DnaJ, and GrpE in an in vitro folding pathway (28) (42) and prolonged DNA damage (41).…”
Section: Resultsmentioning
confidence: 99%
“…GroE is required at all temperatures to aid essential proteins to fold and maintain their proper conformation. Levels of DNA Pol V are dependent on GroE because the chaperon interacts with the polymerase subunit of Pol V and protects it from degradation [25]. Recently we found that GroE is also required for normal and induced levels of Pol IV.…”
Section: The Heat-shock Responsementioning
confidence: 99%